Irritações no espaço do quinto poder: Ritos e fragmentos de construção da crítica de mídia no observatório da imprensa - Garcia, Adriana Domingues (Universidade do Vale do Rio dos Sinos, 2012)
This work has as its theme the relationship between mediatization, digital technologies, interactions and critical media. The study object seized consists of changes to the website of the Observatório da Imprensa (OI), from the beginning of june 2011, which constituted reconfigurations in the formation of critical media, due to expansion of the circulation loop intermedia and intramedia. The objectives are to examine the movements caused this circulation, seeking relationships between the dimensions semiointeractional and techno-technological procedurals in the discussions and shares media between individuals media on the internet. We analyze the modalities of interactions conducted at the site of OI, in relation to their modes semio-tech-technology, as an articulation between mediatization and criticism of media, articulating the vision system self fortified by autopoiesis, where they occur self referentiality and straight referentiality (LUHMANN, 2005). The methodological perspective is anchored in the Movement Ascending, Descending and Construction of Circular Object Empirical Research (FERREIRA, 2010), in order to make contact with those observed during the selection of evidence to build a collection relevant, considering an angle determined. The corpora were made at various times of the research around topics most relevant for quantitative analysis of the object under construction. Basically, it's articles and their comments around the same in different technological situations and /or responding to movements in the development of updated methodological research.The analyzes showed that in the space of OI there is ring-fenced processes, prepared by the participants of the interaction with the potential to stimulate debate. We found in contrast to Luhmann, the autonomy of this autopoietic process does not end with difference and irritation of the environment. Autonomy is not the environment in determining the system, however, are mainly in irritation / structural couplings, which then become reflective fragments, where important changes occur in social construction.
Keywords: Midiatização; Crítica de mídia; Dispositivos midiáticos; Sistemas autofortificados; Observatório da imprensa; Mediatization; Media criticism; Media devices; Systems self dortified; ACCNPQ::Ciências Sociais Aplicadas::Comunicação